2010
DOI: 10.1016/j.chom.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mechanisms of Vaccine-Induced Protection against HPV Infection

Abstract: Summary Using a human papillomavirus (HPV) cervicovaginal murine challenge model, we microscopically examined the in vivo mechanisms of L1 virus-like particle (VLP) and L2 vaccine-induced inhibition of infection. In vivo HPV infection requires an initial association with the acellular basement membrane (BM) to induce conformational changes in the virion that permit its association with the keratinocyte cell surface. By passive transfer of immune serum, we determined that anti-L1 antibodies can interfere with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 44 publications
7
132
0
3
Order By: Relevance
“…This may be because protection of the vaccine is provided through the production of serum neutralizing anti-HPV IgG antibodies binding to viral particles, [17][18][19] which only requires small amounts of antibody to be present. 20,21 One interesting finding was that vaccinated young adult women had a higher prevalence than unvaccinated women of www.tandfonline.comhigh-risk types other than HPV 16 and 18, and thus are still at risk of cervical cancer and other HPV-related cancers. This is consistent with clinical trials on the quadrivalent vaccine which showed it provided some protection against HPV 31 and 59, but not other types.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may be because protection of the vaccine is provided through the production of serum neutralizing anti-HPV IgG antibodies binding to viral particles, [17][18][19] which only requires small amounts of antibody to be present. 20,21 One interesting finding was that vaccinated young adult women had a higher prevalence than unvaccinated women of www.tandfonline.comhigh-risk types other than HPV 16 and 18, and thus are still at risk of cervical cancer and other HPV-related cancers. This is consistent with clinical trials on the quadrivalent vaccine which showed it provided some protection against HPV 31 and 59, but not other types.…”
Section: Discussionmentioning
confidence: 98%
“…Details about NHANES can be found elsewhere. 27 Our study included young adult women (20)(21)(22)(23)(24)(25)(26) was first approved for use in 2006, all women in this age range would have received the vaccine after 12 years of age. This age group was selected because few data are available on those vaccinated after the recommended age of 11-12 years.…”
Section: Methodsmentioning
confidence: 99%
“…The first receptor, a heparin sulfate proteoglycan, is on the basement membrane and binds to the outer L1 protein coat of the HPV virion (Fig. 2) [29]. This binding causes a transformational change in the outer protein coat allowing the L2 proteins to be exposed through the L1 layer.…”
Section: Natural History Of Hpv Infectionsmentioning
confidence: 99%
“…High antibody titers prevent interaction with the basement membrane receptor. Low antibody titers can only prevent interaction if there is high avidity [29]. HPV human papilloma virus; HSPGs heparan sulfate proteoglycans (From Day et al [29], with permission.)…”
Section: Clinical Value Of Prophylactic Hpv Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation